IMMUNE AND METABOLIC PHENOTYPES OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN MEN - E. P. Kalinina (SPb RAACI, 2014)
This review concerns studies of compensatory mechanisms in the antioxidant defense, intensification of lipid peroxidation products, assays of local and systemic cytokine profile in COPD patients, thus allowing to determine the molecular phenotypes of systemic inflammatory response. The first of these phenotypes is characterized by certain biomarker combination, i.e., balanced lipid peroxidation and antioxidant defense system, many-fold increase in tissue and systemic concentrations of TFG-β1, high TNFα level. This phenotype is characterized by a moderate immunosuppression, balanced inflammation in respiratory tract. A set of biomarkers typical to the second phenotype may be characterized by activation of free radical lipid oxidation, high levels of of TNFα, bFGF and TGF-β1 secretion, increased sTNFα RI (p55), along with decreased synthesis of a chemoattractant IL-8 cytokine. This phenotype is characterized by an immunosuppressive imbalance causing inflammation in respiratory tract. The third phenotype is associated with the following biomarkers: inactivation of peroxidation processes, high-level secretion of TNFα, bFGF, and sTNFα RI (p55) and decreased TGF-β1 and IL-8 synthesis, thus resulting into imbalanced immunodeficient inflammation in respiratory tract.